Unveiling the signal valve specifically tuning the TGF-β1 suppression of osteogenesis: mediation through a SMAD1-SMAD2 complex - Ying-Wen Wang; Ching-Wei Luo (Cell Communication and Signaling)
Abstract Background TGF-β1 is the most abundant cytokine in bone, in which it serves as a vital factor to interdict adipogenesis and osteogenesis of bone marrow-derived mesenchymal stem cells (BM-MSCs). However, how TGF-β1 concurrently manipulates differentiation into these two distinct lineages remains elusive. Methods Treatments with ligands or inhibitors followed by biochemical characterization, reporter assay, quantitative PCR and induced differentiation were applied to MSC line or primary BM-MSCs for signaling dissection. In vivo adipogenesis and ex vivo culture of bone explants were used to verify the functions of different SMAD complexes. Ingenuity Pathway Analysis, and analysis of transcriptomic datasets from human BM-MSCs in combination with hierarchical clustering and STRING assay were used to decipher the interplaying co-repressors. Mouse models of chronic and acute bone loss followed by biochemical assays and micro-computed tomography demonstrated the bone effects when functionally blocking the critical co-repressor HDAC1. Results Distinct from the TGF-β1 inhibition on adipogenesis through canonical SMAD2/3 signaling, we clarified that TGF-β1 suppresses osteogenesis by inducing the formation of previously unidentified mixed SMADs mainly composed of SMAD1 and SMAD2, in which SMAD2 recruits more TGF-β1-induced co-repressors including HDAC1, TGIF1 and ATF3, whereas SMAD1 allows directing the whole transcriptional suppression complex to the cis-elements of osteogenic genes. Depletion of the cross-activation to the mixed SMADs dismantled specifically the TGF-β1 suppression on osteogenesis without affecting its inhibition on adipogenesis. Such phenomena can be reproduced via knockdown of co-repressors such as Hdac1 or addition of HDAC1 inhibitors in TGF-β1-treated MSCs. In either the chronic or the acute bone loss model, we demonstrated that the TGF-β signaling was augmented in the bone niche during osteolysis, whereas administration of HDAC1 inhibitors significantly improved bone quality. Conclusion This study identifies a new signal valve through which TGF-β1 can inhibit osteogenesis specifically. Functional interruption of this valve can tilt the seesaw balance of BM-MSC differentiation towards osteogenesis, highlighting the interplaying co-repressors, such as HDAC1, as promising therapeutic targets to combat diverse degenerative orthopedic diseases.